2014
DOI: 10.1038/bjc.2014.39
|View full text |Cite
|
Sign up to set email alerts
|

Guanine nucleotide exchange factor Dock7 mediates HGF-induced glioblastoma cell invasion via Rac activation

Abstract: Background:Glioblastoma multiforme (GBM), a highly invasive primary brain tumour, remains an incurable disease. Rho GTPases and their activators, guanine nucleotide exchange factors (GEFs), have central roles in GBM invasion. Anti-angiogenic therapies may stimulate GBM invasion via HGF/c-Met signalling. We aim to identify mediators of HGF-induced GBM invasion that may represent targets in a combination anti-angiogenic/anti-invasion therapeutic paradigm.Methods:Guanine nucleotide exchange factor expression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…Of note is that DOCK1 also plays a central role in the aforementioned EGF-promoted EGFR-DOCK180/ELMO1-RAC1-MLK3-JNK signaling axis [66]. Additionally, DOCK 7 is reported to play a critical role in the invasive behavior of the glioblastoma and mediates Rac1 activation following HGF stimulation [90]. Another Rac GEF that promotes Rac1-mediated invasion in glioblastoma cells is PREX1, which is overexpressed in GBM and responds to the presence of the upregulated Pi3K pathway [91].…”
Section: Upstream Regulatorsmentioning
confidence: 99%
“…Of note is that DOCK1 also plays a central role in the aforementioned EGF-promoted EGFR-DOCK180/ELMO1-RAC1-MLK3-JNK signaling axis [66]. Additionally, DOCK 7 is reported to play a critical role in the invasive behavior of the glioblastoma and mediates Rac1 activation following HGF stimulation [90]. Another Rac GEF that promotes Rac1-mediated invasion in glioblastoma cells is PREX1, which is overexpressed in GBM and responds to the presence of the upregulated Pi3K pathway [91].…”
Section: Upstream Regulatorsmentioning
confidence: 99%
“…A proteome study has shown that Rac1 protein levels are increased in high‐grade (85%) versus low‐grade (20%) gliomas and correlate with poor survival (Iwadate, ; Salhia et al, ). Direct or indirect depletion of Rac1 significantly inhibits glioblastoma cell invasion (Chuang et al, ; Murray et al, ), indicating the importance of this GTPase in glioblastoma invasiveness.…”
Section: Malignant Alterations Of Glioma Cells Increase Their Invasionmentioning
confidence: 99%
“…Although, we did not find an increase in resorption at 52 wks dynamically or by bone turnover markers/gene expression in our study, it remains unclear whether higher SNS tone is responsible for the non-cell autonomous effects on bone with age in m/m [43]. In fact, Dock7 has been studied for its role in brain and nervous system [8, 9, 14, 18, 19, 44, 45], but it remains unclear if any of these alterations in the nervous system may affect bone development or remodeling. Propranolol treatment, a β2AR antagonist, has been shown to partially rescue m/m bone phenotype in young mice, suggesting that the SNS may indeed be contributing to bone loss in the m/m [4].…”
Section: Discussionmentioning
confidence: 73%